2014
DOI: 10.7860/jcdr/2014/8519.4611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Intensity on Lipid Profile in Sedentary Obese Adults

Abstract: This study suggests that exercise is "elixir" for a healthy life. High intermittent intensity can be considered for individuals who have time constraints and lead a sedentary life style and moderate intensity exercise advised for individuals who are willing to create time for their health benefits. A programmed protocol of exercise will help in reduction of lipid parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 13 publications
3
40
0
4
Order By: Relevance
“…Morio et al (2004) demonstrated that VLDL-TG turnover was increased during and after moderate-intensity exercise in young sedentary subjects. Our findings were also consistent with previous studies which find that exercise alone could significantly reduce TC and LDL-C levels (Berg et al, 2003;Heath et al, 1983;Kannan et al, 2014). Heath et al (1983) also found that moderate intensity exercise for 6 months could not only improve TC and LDL-C levels, but also TG and HDL-C levels in a patients with coronary artery disease.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Morio et al (2004) demonstrated that VLDL-TG turnover was increased during and after moderate-intensity exercise in young sedentary subjects. Our findings were also consistent with previous studies which find that exercise alone could significantly reduce TC and LDL-C levels (Berg et al, 2003;Heath et al, 1983;Kannan et al, 2014). Heath et al (1983) also found that moderate intensity exercise for 6 months could not only improve TC and LDL-C levels, but also TG and HDL-C levels in a patients with coronary artery disease.…”
supporting
confidence: 82%
“…Heath et al (1983) also found that moderate intensity exercise for 6 months could not only improve TC and LDL-C levels, but also TG and HDL-C levels in a patients with coronary artery disease. Meanwhile, Kannan et al (2014) found that 15 weeks of moderate intensity cycling significantly improved TC, TG, LDL-C and HDL-C levels in obese adults. It was believed that the extensive improvement of lipid profile in these previous studies were due to the long period of intervention study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings can be related to physical activity in association with health and nutritional counseling. Research conducted with an obese and sedentary population after 15 weeks of physical exercise demonstrated significant increase in HDL levels and decrease in total cholesterol (19) , confirming that physical exercise causes changes in lipid parameters (19) . Significant differences in WHR and HQ were also observed in IGa participants.…”
Section: Discussionmentioning
confidence: 92%
“…Low intensity exercise done for longer periods uses fat as the substrate for energy, whereas high intensity exercise uses carbohydrate rather than fat. Recently high intensity intermittent exercise had been highlighted for the purpose of weight reduction and lowering atherogenic index [207]. The advantage of high intensity exercise which has been stated is, the shorter duration of activity which is reported to having better long term adherence rate.…”
Section: Lipid Profilementioning
confidence: 99%